Whatsapp: Learning on the go - Pratika Ayuningtyas (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
Mobile learning as one of digital teaching learningmedia has given beneficial impact to language learning. It said that mobile learning can facilitate students to learn everywhere in anytime. Learning using smartphone is one of the issues that can help the students to improve their English whenever they want and wherever they are. Whatsapp as one of the most accessed application, which can be installed in any smartphone is used in this research. The objective of the study is to find out what are the impact of using Whatsapp by exploring, describing and analyzing students opinion in learning English through Whatsapp. This research was conducted in the academic year 2017 / 2018 in the Second Year Class of the Department of Business Administration of Politeknik Sawunggalih Aji. There are 10 students in the classroom. The descriptive qualitative method is used in this research. The result of this research proved some activities done by the students via Whatsapp is showing language learning activities, such as vocabulary learning and combining words to sentence.